KOMBINASI PULSED SHORTWAVE THERAPY DAN NEURODYNAMIC MOBILIZATION LEBIH EFEKTIF MENURUNKAN DISABILITAS PUNGGUNG DIBANDINGKAN KOMBINASI PULSED SHORTWAVE THERAPY DAN LUMBAR SPINE STABILIZATION EXERCISE PADA PASIEN HERNIA NUKLEUS PULPOSUS LUMBOSAKRAL - Satria Nugraha, Made Hendra; Purnawati, Susy; Irfan, Muh.; Handari Adiputra, Luh Made Indah Sri; Muliarta, I Made; -, Wahyuddin (Sport and Fitness Journal; Volume 7, No.1, Januari 2019, 2019)
ABTSRACT Introduction: Herniated Nucleus Pulposus (HNP) is a pathological condition in which there is protrusion of the annulus fibrosus and nucleus pulposus into the lumen of the vertebral canal. Objective: The goal of this study is to determine the effectiveness of combination of pulsed shortwave therapy and lumbar spine stabilization exercise with combination of pulsed shortwave therapy and neurodynamic mobilization in decreasing low back disability in lumbosacral herniated nucleus pulposus patients at Denpasar and Badung Physiotherapy Clinic. Methods: The study used was an experimental method. Pre-test and post-test control group design is the design of this study. This study used 28 subjects were divided into two groups. The control group consist of 14 subjects received a combination of pulsed shortwave therapy and lumbar spine stabilization exercise while the treatment group consist of 14 subjects received a combination of pulsed shortwave therapy and neurodynamic mobilization. Intervention is given 2 times a week for 4 weeks. Sampling methods used in this study was simple random sampling. The low back disability is measured by a modified oswestry disability index. Result: The normality test of the data was tested using Saphiro-Wilk Test and homogeneity test of the data was tested with Levene's Test. Wilcoxon sign rank test results obtained significant differences in the control group with the value of p = 0.001, as well as in the treatment group found a significant difference with the value of p = 0.001. Post-test results with mann-whitney u-test showed a significant difference between the control group and the treatment group where p = 0.044 with the percentage of 48.53% in the control group and 54.88% in the treatment group. Conclusion: Based on the results of this study it can be concluded that the combination of pulsed shortwave therapy and neurodynamic mobilization is more effective than the combination of pulsed shortwave therapy and lumbar spine stabilization exercise in reducing low back disability in patients with lumbosacral herniated nucleus pulposus at the Denpasar and Badung Physiotherapy Clinic. Keywords: lumbosacral herniated nucleus pulposus, low back disability, pulsed shortwave therapy, neurodynamic mobilization, lumbar spine stabilization exercise